Late clinical and magnetic resonance imaging follow up of Nipah virus infection - Lim, C C T; Lee, W L; Leo, Y S; Lee, K E; Chan, K P; Ling, A E; Oh, H; Auchus, A P; Paton, N I; Hui, F; Tambyah, P A (Journal of neurology, neurosurgery and psychiatry, 2003)
The Nipah virus is a newly identified paramyxovirus responsible for an outbreak of fatal encephalitis in Malaysia and Singapore. This paper reports the follow up clinical and magnetic resonance imaging findings in 22 affected subjects. Of 13 patients with encephalitis, one died, one was lost to follow up, and seven recovered. Among the four remaining patients, one had residual sixth nerve palsy, another suffered from severe clinical depression, and a third patient had evidence of retinal artery occlusion. One patient with delayed onset Horner syndrome had a single lesion in the cervical spinal cord. The brain magnetic resonance findings were stable or improved in nine patients over 18 months of follow up. Among a second group of nine asymptomatic seropositive abattoir workers, magnetic resonance examination in seven subjects revealed discrete small lesions in the brain; similar to those detected in encephalitis patients. These findings suggest that in addition to encephalitis, the newly discovered Nipah virus affects the spinal cord and the retina. Late clinical and radiological findings can occur in Nipah virus infections as with other paramyxoviruses.